Enhancing Emotional Intelligence in Pervasive Developmental Disorders. The Autism Paradigm - Kalogeratos, Gerasimos; Anastasopoulou, Eleni; Stavrogiannopoulos, Anastasios; Tsagri, Angeliki; Tsogka, Danai; Lourida, Konstantina (Technium Education and Humanities, 2023)
Pervasive Developmental Disorders (PDD), which include various conditions falling under the Autism Spectrum, are frequently characterized by difficulties in social communication. The presence of emotional intelligence (EI), which plays a crucial role in the comprehension and regulation of emotions within oneself and others, may occasionally be diminished in individuals diagnosed with Pervasive Developmental Disorders (PDD). This study examines various approaches to augmenting Emotional Intelligence (EI) in individuals with Pervasive Developmental Disorders (PDD). Additionally, it investigates the potential leadership capabilities that can be unlocked due to this augmentation. The literature acknowledges the inherent strengths of individuals with PDD, including their analytical capabilities and unique perspectives. However, enhancing their emotional intelligence (EI) can provide them with additional skills necessary for assuming leadership positions. The utilization of structured learning, experiential environments, and mindfulness practices has demonstrated potential in augmenting emotional intelligence (EI), thus enabling individuals with Pervasive Developmental Disorders (PDD) to leverage their inherent strengths more effectively in leadership settings. This highlights the necessity of implementing a comprehensive leadership development program specifically designed to address the unique requirements of individuals with Pervasive Developmental Disorders (PDD), thereby promoting a more inclusive approach to leadership.